2015
DOI: 10.1155/2015/629587
|View full text |Cite
|
Sign up to set email alerts
|

Single-Fraction Radiotherapy for CD30+Lymphoproliferative Disorders

Abstract: Objectives. CD30+ lymphoproliferative disorder is a rare variant of cutaneous T-cell lymphoma. Sustained complete response following first-line treatments is rare. This retrospective review evaluates the response of refractory or recurrent lesions to palliative radiation therapy. Methods. The records of 6 patients with 12 lesions, treated with radiation therapy, were reviewed. All patients received previous first-line treatments. Patients with clinical and pathological evidence of symptomatic CD30+ lymphoproli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Other authors 15 Our experience is comparable to the data of the literature: at the moment, our prescription of dose is 25 Gy, but we are trying to administer the lowest dose possible particularly in the localization of the face. Moreover, if we analyze our series dividing it into two groups of patients numerically homogeneous ( Figure 3 Five-year local control rate and relapse-free rate after radiation therapy in 30 patients with PCALCL in the treatment of solitary or localized disease and a possible approach in multifocal presentation when lesion number is ≤5.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Other authors 15 Our experience is comparable to the data of the literature: at the moment, our prescription of dose is 25 Gy, but we are trying to administer the lowest dose possible particularly in the localization of the face. Moreover, if we analyze our series dividing it into two groups of patients numerically homogeneous ( Figure 3 Five-year local control rate and relapse-free rate after radiation therapy in 30 patients with PCALCL in the treatment of solitary or localized disease and a possible approach in multifocal presentation when lesion number is ≤5.…”
Section: Discussionsupporting
confidence: 77%
“…Other authors have discussed the theme of single‐fraction radiotherapy in CD30 + lymphoproliferative disorders in their six patient series which also included patients with lymphomatoid papulosis (LYP). The targets were symptomatic lesions or recurrences, and they did observe no difference in response between the group treated with single fraction of 7.5–8 Gy and the group treated with multiple fractions of 2–2.5 Gy to the total dose of 40–46 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, doses lower than 30 Gy were associated with complete responses, suggesting that the minimal recommended dose may be <30 Gy. The efficacy of lower doses is further supported by Gentile et al (12), who reported a 100% CCR for pcCD30 + LPD treated with a single fraction of 7.5 to 8 Gy. This study included mostly patients with LyP, in which spontaneous regression without treatment is well documented.…”
Section: Discussionmentioning
confidence: 79%
“…In cases that manifest with numerous papules or nodules and/or common recurrence, low-dose methotrexate (5-20 mg/week) is the most effective therapy, but the disease often relapses after discontinuation of treatment. Beneficial therapeutic effects have also been reported with PUVA and topical nitrogen mustard (Table V) (Kempf et al, 2011;Duvic et al, 2015;Gentile et al, 2015;Wieser et al, 2015). In PCALCL, radiotherapy or surgical excision are the firstline treatments for patients with solitary or localized skin • Primary cutaneous CD4+ small/medium-T-cell lymphoproliferative disorder…”
Section: Prognosis and Treatment Optionsmentioning
confidence: 99%
“…In cases of disseminated/multifocal disease, low-dose methotrexate is usually recommended, and doxorubicinbased multiagent chemotherapy is used in rare cases with extracutaneous involvement or rapidly progressing tumours (Table V) (Kempf et al, 2011;Gentile et al, 2015). Brentuximab vedotin is the best systemic therapy based on the high expression of CD30 on the neoplastic cells .…”
Section: Prognosis and Treatment Optionsmentioning
confidence: 99%